Renal Function in Patients with Acute Myocardial Infarction: A Current Perspective. - Hedgar, Berty Gutiérrez (Journal of Patient Care and Services, 2018)
A clinical perspective on renal function in acute myocardial infarction reviews pathophysiology, prognostic markers, and management implications, including contrast nephropathy prevention and hemodynamic support.
Keywords: Acute myocardial infarction; glomerular filtration; renal insufficiency; mortality; creatinine.